Displacement and (Post)memory in Post-Soviet Women’s Writing - Sorvari, Marja. author. (orcid)0000-0002-3311-726X Link aut Link
IX, 167 p.
Keywords: The book examines prominent literary works from the past two decades by Russian women writers dealing with the Soviet past. It explores works such as Daniel Stein, Interpreter by Ludmilla Ulitskaya, The Time of Women by Elena Chizhova, Secondhand Time: The Last of the Soviets by Svetlana Alexievich, and In Memory of Memory by Maria Stepanova, and uncovers connecting thematic structures and features. Focusing on the concepts of displacement and postmemory, the book shows how these works have given voice to those on the margins of society and of ‘great history’ whose resistance was often silent. In doing so, these women writers portray the everyday experiences and trauma of displaced women and girls during the second half of the twentieth century. This study offers new insights into the importance of these women writers’ work in creating and preserving cultural memory in post-Soviet Russia. Marja Sorvari is Associate Professor of Russian Language and Culture at the University of Eastern Finland. She specializes in contemporary Russian literature and gender studies. She is author of About the Self and the Time: On Autobiographical Texts by Maria Arbatova, Elena Bonner, Ėmma Gerštejn, Tamara Petkevič and Maija Pliseckaja (2004) and has co-edited several volumes.